Birthweight and its association with cardiometabolic risk parameters in rural Maya children from Yucatan, Mexico - Julio Lara-Riegos; Hugo Azcorra; Juan Carlos Salazar-Rendón; Víctor Arana-Argáez; María Teresa Castillo-Burguete; Nina Mendez-Dominguez (Annals of Human Biology)
Background Knowledge about the influence of early developmental factors on cardiometabolic health in the Maya is limited.Aim To analyse the relationship between birthweight (BW) and cardiometabolic parameters in a sample of rural Maya children from Yucatan, Mexico.Subjects and methods We took anthropometric measurements and obtained data on BW and fasting blood samples in a sample of 75 children aged 5–14 years. Dependent variables were: fat mass index (FMI), body mass index (BMI), glucose (G), triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL), low-density lipoprotein cholesterol (LDL), LDL/HDL and TC/HDL ratios and metabolic index (TGxG/HDL2). Outcomes were transformed to y = 100 log(e)x and the resulting estimates are interpreted as symmetrical percentage differences. The main independent variable was BW z-score. Multiple linear regression analyses were used to assess the relationship between BW and outcomes.Results An increase of one standard deviation in BW predicted 6.6% (95% CI [–11.6, −1.6]) decrease in HDL and 11% (95% CI [3.7, 18.4]), 7.8% (95% CI [2.3, 13.2]) and 19.6% (95% CI [3.1, 36]) increases in LDL/HDL, TC/HDL and metabolic index, respectively.Conclusion Higher birthweights were associated with adverse levels of biochemical parameters in this sample of rural Maya children.